Supply chain sustainability and risk management in food cold chains: A literature review - Raja Usman Khalid; Muhammad Shakeel Sadiq Jajja; Muhammad Bilal Ahsan (Modern Supply Chain Research and Applications, 2024)
Purpose - This article aims to evaluate published food cold chain (FCC) literature against risk management and supply chain sustainability concepts. Design/methodology/approach - The article uses the theory refinement logic proposed by Seuring et al. (2021) to analyze the contents of FCC management-related literature published over the past 20 years. A sample of 116 articles was gathered using Web of Science and subsequently analyzed. The respective articles were then systematically coded against the frameworks of Beske and Seuring (2014) and Vlajic et al. (2012), which focused on building sustainable and robust supply chains, respectively. Findings - The literature review revealed that debates around managing contemporary sources of disruptions/vulnerability and making FCCs more sustainable and resilient are gradually developing. However, an overarching risk management perspective along with incorporating social and environmental dimensions in managing FCCs still needs the adequate attention of the respective research community. Research limitations/implications - The deductive internal logic of theory refinement approach used in this paper could have been further strengthened by using additional frameworks. This limitation, however, opens avenues for further research. The findings of the paper will stimulate the interest of future researchers to work on expanding our understanding related to sustainability and risk management in FCCs. Originality/value - The paper is the first attempt to organize published FCC literature along dimensions of supply chain sustainability and risk management. The paper thus provides the respective researchers with a foundation that will help them adopt a focused approach to addressing the research gaps.
Keywords: 650; Food cold chain (FCC); Sustainable supply chain management (SSCM); Literature review; Vulnerability; Risk management